Assessing research participant preferences for receiving study results. Issue 3 (4th June 2020) - Cook, Sarah; Mayers, Stephanie; Goggins, Kathryn; Schlundt, David; Bonnet, Kemberlee; Williams, Neely; Alcendor, Donald; Barkin, Shari
Abstract: Introduction: Dissemination of results to research participants is largely missing from the practices of most researchers. Few resources exist that describe best practices for disseminating information to this important stakeholder group. Methods: Four focus groups were conducted with a diverse group of individuals. All participants were part of a Patient-Centered Outcomes Research Institute-funded survey study. Focus groups aimed to identify participants' preferences about receiving research results and their reactions to three different dissemination platforms. Results: Four focus groups with 37 participants were conducted, including: (1) adults with one comorbidity, at least a college education, and high socioeconomic status (SES); (2) adults with one comorbidity, less than a college education, and lower SES; (3) adults with low health literacy and/or numeracy; and (4) Black or African American adults. Participants discussed their preferences for research results delivery and how each of the platforms met those preferences. This included information needs as they relate to content and scope, including a desire to receive both individual and aggregate results, and study summaries. Email, paper, and website were all popular avenues of presentation. Some desired a written summary, and others preferred videos or visual graphics. Importantly, participants emphasized the desire for having a choice in the timing, frequency, and types of results. Conclusion: Research participants prefer to receive research results, including study impact and key findings, disseminated to them in an engaging format that allows choice of when and how the information is presented. The results encourage new standards whereby research participants are considered a critical stakeholder group.